Understanding uniqueness and diversity in child and adolescent mental health - Hodes, Matthew; Shur-Fen Gau, Susan; De Vries, Petrus J. (Academic Press, 2018)
Understanding Uniqueness and Diversity in Child and Adolescent Mental Health examines the determinates of individual differences in children and young people, along with the origins of maladjustment and psychiatric disorders. It addresses the ways in which interventions and mental health services can be developed and shaped to address individual differences amongst children. Topics cover the influence of economic adversities and gender differences on child development and life course, as well as the range of risk and protective factors associated with the onset and persistence of problems, including sections on anxiety disorders in infants, bipolar disorder, and tics and Tourette’s. Additional sections focus on the potential for individualizing treatments as illustrated by pharmacogenomics, with another highlighting ways in which services can be adapted for specific environments, such as the needs of refugee children and systems of service delivery that can be enhanced by the use of telemedicine.--Provided by publisher.